If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + -18 = 5y + 3 Reorder the terms: -18 + -2y = 5y + 3 Reorder the terms: -18 + -2y = 3 + 5y Solving -18 + -2y = 3 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -18 + -2y + -5y = 3 + 5y + -5y Combine like terms: -2y + -5y = -7y -18 + -7y = 3 + 5y + -5y Combine like terms: 5y + -5y = 0 -18 + -7y = 3 + 0 -18 + -7y = 3 Add '18' to each side of the equation. -18 + 18 + -7y = 3 + 18 Combine like terms: -18 + 18 = 0 0 + -7y = 3 + 18 -7y = 3 + 18 Combine like terms: 3 + 18 = 21 -7y = 21 Divide each side by '-7'. y = -3 Simplifying y = -3
| 7r-3r+5=1+10-4r | | (x^2-9)(x+2)=0 | | 7x-12+2x+9+2x+9=180 | | 2*f=-46 | | 6x+3+6-2= | | 3/4=45 | | y-0.5y=4.5 | | 9a+8-7= | | 0.2(3+p)=4.6 | | X=1/2(3X-2)+2 | | -16+3n=8n-3(n-4) | | X=1/2(3X-2+2) | | 20y^2=21y-4 | | 3(x+8)-8=3x-19 | | cos^2(4x)+cos(4x)=0 | | X=1/2(3X-2) | | m^2-20=8m | | 7x^2+6x=5 | | X=2(3X-2) | | -6(x-10)=-12 | | 5x^6y^3= | | 25X=2(3X-2) | | -3x-5=4x-6 | | 685=85-2x | | a=bh/2 | | (8+2x)5=-28x+2 | | -4(x+2)=-8 | | 1.5(2e-30)+2e=135 | | 3.7j+1.9=16.7 | | (16a^5b^-5)^-4/(2a^6b^-2)^-4 | | 6-3=x | | 9/103 |